The psyche as behavior (2013)
Behaviorism has argued that behavior is the Psyche and the subject matter of psychology. Although, some scientists had done empirical work with objective methods before 1913, theyear in which John B. Watson published his manifesto, he was the first one to attempt a systematization of behavior as the Psyche, that is, as psychology’s subject matter. In this text, I outline Watson’s notion of behavior to compare it with two other forms of behaviorism: Skinner’s radical behaviorism and molar behaviorism. The purpose of the paper is to illustrate how the concept of behavior has been and is changing.